MAGNETIZATION AND POLARIZATION PROFILE IN PML-TYPE MAGNETOELECTRIC MULTIFERROICS WITH CANTED SPIN SYSTEM - Gunawan, Vincensius; Stamps, Robert L (BERKALA FISIKA, 2012)
We calculate the profile of both magnetization and polarization of a PML-typemagnetoelectric multiferroics which allow the magnetization of sub-lattices to be canted. Â Thecalculation is started by deriving the Landau energy density and followed by solvingsimultaneously three equilibrium equations which respect to polarization, magnetization andcanting angle. Â  It is predicted that magnetoelectricity give rise to a â€œbumpâ€ in polarization profile.Â It is also calculated that the application of a magnetic/an electric field will also influence thepolarization/magnetization of the material.Keywords: Â multiferroics, magnetization and polarisation